Analysis of Thermal Characteristics and Insulation Resistance Based on the Installation Year and Accelerated Test by Electrical Socket Outlets - Kyung Chun Kim; Doo Hyun Kim; Sung Chul Kim; Jae Ho Kim (Elsevier, 2020)
ABSTRACT: Background: Electrical socket outlets are used continuously until a failure occurs because they have no indication of manufacturing date or exchange specifications. For this reason, 659 electrical fires related to electrical socket outlets broke out in the Republic of Korea at 2018 only, an increase year on year. To reduce electrical fires from electrical socket outlets, it is necessary to perform an accelerated test and analyze the thermal, insulation resistance, and material properties of electrical socket outlets by installation years. Methods: Thermal characteristics were investigated by measured the temperature increase of electrical socket outlets classified according to year with variation of the current level. Insulation resistance characteristics was measured according to temperature for an electrical socket outlets by their years of use. Finally, to investigate the thermal and insulation resistance characteristics in relation to outlet aging, this study analyzed electrical socket outlets' conductor surface and content, insulator weight, and thermal deformation temperature. Results: Analysis showed, regarding the thermal characteristics, that electrical socket outlet temperature rose when the current value increased. Moreover, the longer the time that had elapsed since an accelerated test and installation, the higher the electrical socket outlet temperature was. With respect to the insulation resistance properties, the accelerated test (30 years) showed that insulation resistance decreased from 110 °C. In relation to the installation year (30 years), insulation resistance decreased from 70 °C, which is as much as 40 °C lower than the result found by the accelerated test. Regarding the material properties, the longer the elapsed time since installation, the rougher the surface of conductor contact point was, and cracks increased. Conclusion: The 30-year-old electrical socket outlet exceeded the allowable temperature which is 65 °C of the electrical contacts at 10 A, and the insulation resistance began to decrease at 70 °C. It is necessary to manage electrical socket outlets that have been installed for a long time.